Evaluating the resolving disputes practices of Lupong Tagapamayapa: : Constituents’ view from Barangay Bual Sur, Midsayap, Cotabato, Philippines - Yasser Andan; Gideon Sumayo (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
Purpose – This paper aims to assess how the Lupong Tagapamayapa is effective in resolving disputes, based on the perceptions of local residents in Barangay Bual Sur, Midsayap, Cotabato, Philippines. It also explores whether socio-demographic factors influence how people view the system’s effectiveness.Methodology/approach – A descriptive-correlational approach was used. A total of 114 individuals who had experienced dispute resolution through the Lupong Tagapamayapa were selected through purposive sampling. Respondents rated the system’s performance in four areas: understanding of the barangay justice system, clarity of procedures, decision-making, and interpersonal skills. Correlation analysis was conducted to examine links between demographic traits and perceptions of effectiveness. Findings – Findings revealed a positive but weak relationship between age and perceived effectiveness across all domains, with correlation coefficients ranging from r = 0.297 to r = 0.349 (p ≤ 0.001), and older constituents tending to view the system more favorably. In contrast, sex and employment status were not significantly associated with perceptions of effectiveness (p > 0.05). The Lupong Tagapamayapa was rated highly effective, with overall domain means ranging from 3.877 to 3.916 (on a 1–5 scale).Novelty/value – Local justice systems play a fundamental and pivotal role in community peacebuilding. Our findings stress not only the strengths of the Lupong Tagapamayapa, particularly in legal knowledge and interpersonal skills, but also the importance of engaging younger members of the community more actively. The study supports the need for sustained training and awareness efforts at the barangay level.